The fast track project: the first step towards improving divorce cases in Shariah Court, Malaysia / Farah Safura Muhammud - Muhammud, Farah Safura (2020)
Shariah Court is an institution that plays an important role in governing divorces in Malaysia. The increase of divorce cases that occur in Malaysia pressurizes the Shariah Court in some ways. The administration of these divorce cases needs to be administered more effectively to ensure the smoothness of each case. This study was done to investigate and identify the most registered cases in the Shariah Court in Malaysia. In addition, this study serves to identify the workflow for the newly introduced project concerning divorce cases called "the fast track". This will help to overcome the divorce case backlogs that will happen in the future. To ensure the success of this study, a number of employees has been interviewed, ranging from the judges, attorneys and assistant registrars for the Shariah Court. The results of the study showed that enactment section 47, Islamic Family Law is among the most registered cases and constantly increasing every year. The fast track is seen as a good method, but some things need to be taken care of to ensure its effectiveness. Consistent work force is also required to ensure this fast project achieves its potential in administering divorce cases in the Shariah courts.